The Influence Of Corporate Governance On Firm Performance: A Comparison Between Banks And Insurance Companies - Loh, Yunn Cinn (2021)
The purpose of this paper is to identify the relationships between corporate governance mechanisms and performance of the financial institutions in terms of risk management. The sample is based on a panel dataset of public listed banks and insurance companies in the context of 10 Asian countries over a five year period, from 2015 to 2019. By employing panel data analysis and stepwise regression, empirical results show that banks’ performance is solely affected by ownership structure. Meanwhile, insurance companies’ performance is affected by board characteristics (board independence and board meeting), audit committee size and ownership structure. Therefore, it can be concluded that banks’ risk taking behaviour is not influenced by corporate governance mechanisms as much as insurance companies do as insurers are overall affected by the internal corporate governance variables and ownership structure. This study contributes to the existing literature and enriches the understanding of corporate governance in constraining risk taking behaviour in a sector with significantly complex context.